Acute and Subchronic Toxicity Profile of Euphorbia pulcherrima Methanol Extract on Wistar Albino Rats. (19th February 2015) - Sharif, H. B.; Mukhtar, M. D.; Mustapha, Y.; Baba, Gabi; Lawal, A. O.
Abstract : This work was designed to evaluate the acute and subchronic toxicity of E. pulcherrima methanol extract. Mean lethal dose (LD50 ) and subchronic toxicity were determined using Lorke's method to assess the effect of the extract on kidney and liver functions along histopathology assessment of the liver and kidney, respectively. The LD50 determined was 3807.89 mg/kg both orally and intraperitoneally. The kidney function parameters indicated elevation of the serum urea above the normal value in both control and the group treated with 10 mg/kg of the extract with mean values of 7.92 ± 1.19 and 7.86 ± 1.14 mMol/L, respectively. The creatinine and electrolytes were within the normal values. The results of ALAT, ASAT, ALP, T protein albumin, and bilirubin in all cases were within the normal values. Kidney, liver function parameters, and relative organ weight were statistically insignificant across all groups. This shows that various concentrations of E. pulcherrima extract did not influence negatively the liver and kidney function parameters. Further studies are required to rule out the observed mild hepatic histological changes among a few members of the groups treated with 100 and 1000 mg/kg/day and any possible hepatoprotective and nephron-protective potential the extract may possess.